Study on the fire characteristics of the compartment with two opposing openings under external sideward wind. (June 2022) - He, Mingming; Hu, Haowei; Ji, Jie; Chen, Shuo; Meng, Xiangmin; Gao, Zihe; Li, Man
Abstract: This paper investigated the spill flame behavior and temperature distribution for the compartment with two opposing openings under the effect of sideward wind. The experiment was carried out in a reduced-scale cubic compartment with two opposing openings (window and door). The sideward wind speed ranged from 0 to 4 m/s. The experimental results show that when the heat release rate (HRR) is relatively small, intermittent flame occurs outside the window, and the smoke plume spills out from the upper part of the door. The flame projection probability near the window increases first and then decreases with the increase of sideward wind speed. With the increase of HRR, continuous flame presents outside the window and intermittent fire plumes overflow together with the smoke plume from the door. As the sideward wind speed increases, the lowest location of the continuous flame ejected from the window drops. The height and horizontal extending distance of continuous flame are also affected by the window size. Besides, the experiment reveals that as the wind speed increases, the temperature at the windward (exposed to the wind) near the window decreases, while the temperature gradients at the leeward (away from the wind) in vertical direction almost disappear.